PENGARUH MEDIA RODA ANGKA TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 4-5 TAHUN DI TK ISLAM FATIMAH KECAMATAN TAMPAN KOTA PEKANBARU - Imelda, Imelda; Zulkifli N, Zulkifli N; Kurnia, Rita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the effect of media on the number wheel the the ability to know the concept of number of children aged 4-5 years in TK Islam Fatimah in sub district Tampan of Pekanbaru City. The research used experimental method with one group pre-test post-test design. The sample used in this study were 15 students. The data collection technique used is observation. Technique of data analysis using t-test test by using program of SPSS 16. Research hypothesis that there is the effect of media on the number wheel the the ability to know the concept of number of children aged 4-5 years in TK Islam Fatimah in sub district Tampan of Pekanbaru City. Based on data analysis known tcalculated = 10,315> ttable = 2,145 with Sig. (2-tailed) = 0.000. Because Sig <0,05 it can be concluded that there are differences in the ability to recognize the concept of numbers before and after the media on the number wheel. It can be interpreted that there is the effect of media on the number wheel the ability to know the concept of number of children aged 4-5 years in TK Islam Fatimah in sub district Tampan of Pekanbaru City significant as much as 50,87%.Keyword: Ability to know the concept of numbers, Media on the number wheel